Identifikasi Peserta Didik Berkebutuhan Khusus (PDBK) Hambatan Emosional (Tunalaras) di Sekolah Dasar - Siti Nuranisah Siregar; Jesi Alexander Alim; Neni Hermita (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research aims to identify students with special needs (PDBK) with emotional barriers (tunalaras) in elementary schools. Tunalas is a disorder in managing emotions and behavior that has an impact on students' social interactions and learning processes. The method used in this research is descriptive quantitative, with data collection techniques through observation, interviews and documentation. The research results showed that of the 846 students, 11 students (1.30%) were identified as experiencing emotional obstacles. The main characteristics of students with hearing impairments include difficulties in controlling emotions, a tendency to act aggressively, and difficulties in building social relationships. Therefore, a more adaptive and emotional support-based learning approach is needed to help them participate more effectively in inclusive education. By understanding the characteristics of students with disabilities, schools can develop more appropriate learning strategies to improve their academic and social development.